A Note on the Wing Petiole of Sal Seed from Tarai East Forest Division, Haldwani, Uttarakhand - Nimmala, Rohit; Nimmala, Jagrut (Journal of Research in Science and Engineering, 2025)
Sal (Shorea robusta) is a dominant tree species in India's tropical moist and dry deciduous forests. It plays a crucial role in forest ecosystems and biodiversity conservation. This study focuses on the morphological variations in Sal seeds, particularly the rare occurrence of six - winged seeds in the Tarai East Forest Division of Uttarakhand. Field observations across six forest ranges revealed distinct wing patterns, with larger wings measuring between 5.6–7.2 cm and smaller ones between 3.1–4.5 cm. The study found that the occurrence of six - winged Sal seeds varied with temperature, being higher in areas with mean temperatures of 34–39°C. This variation may contribute to improved seed dispersal and natural regeneration, highlighting an adaptive trait of Sal in response to environmental conditions.